2019
DOI: 10.1002/1878-0261.12548
|View full text |Cite
|
Sign up to set email alerts
|

RAC1 inhibition reverses cisplatin resistance in esophageal squamous cell carcinoma and induces downregulation of glycolytic enzymes

Abstract: Development of chemoresistance remains a major challenge in treating esophageal squamous cell carcinoma (ESCC) patients despite treatment advances. However, the role of RAC1 in chemoresistance of ESCC and the underlying mechanisms remain largely unknown. In this study, we found that higher levels of RAC1 expression were associated with poorer prognosis in ESCC patients. Enhanced RAC1 expression increased cell proliferation, migration, and chemoresistance in vitro . Combination therapy us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 78 publications
2
40
0
Order By: Relevance
“…In esophageal squamous cell carcinoma, Rac1 expression was associated with poor prognosis and therapy resistance. Use of the Vav/Rac inhibitor EHop-016 was shown to overcome cisplatin resistance in esophageal squamous cell carcinoma in vitro and in vivo and by decreasing Akt/FOXO3a signaling and glycolysis (Schmit et al, 2019;Zeng et al, 2019), further validating its therapeutic applicability. Moreover, Tiam1 and Rac1 were overexpressed in a 3-D model of lymphoma, where treatment with Tiam1/Rac1 inhibitor NSC23766 overcame chemoresistance to doxorubicin (Ikram et al, 2018).…”
Section: Rac/cdc42 Inhibitors In Therapy Resistancementioning
confidence: 93%
“…In esophageal squamous cell carcinoma, Rac1 expression was associated with poor prognosis and therapy resistance. Use of the Vav/Rac inhibitor EHop-016 was shown to overcome cisplatin resistance in esophageal squamous cell carcinoma in vitro and in vivo and by decreasing Akt/FOXO3a signaling and glycolysis (Schmit et al, 2019;Zeng et al, 2019), further validating its therapeutic applicability. Moreover, Tiam1 and Rac1 were overexpressed in a 3-D model of lymphoma, where treatment with Tiam1/Rac1 inhibitor NSC23766 overcame chemoresistance to doxorubicin (Ikram et al, 2018).…”
Section: Rac/cdc42 Inhibitors In Therapy Resistancementioning
confidence: 93%
“…These include compounds that inhibit GEF-GTPase binding, which have produced promising results in preclinical cancer models. For example, EHop-016 blocks the interaction of Rac1 with Vav2 (Montalvo-Ortiz et al, 2012), and has been shown to enhance the anti-tumor effect of cisplatin in xenograft models of esophageal squamous cell carcinoma (Zeng et al, 2019). ZCL278 blocks the interaction of Cdc42 with intersectin (Friesland et al, 2013) and can inhibit the growth of lung cancer xenografts (Aguilar et al, 2019).…”
Section: Targeting Rho Gtpase Activationmentioning
confidence: 99%
“…And several key proteins in the glycolytic pathway have been discovered as promising targets for overcoming chemoresistance [ 39 41 ]. It was reported that suppressing glycolytic enzymes by inhibiting RAC1 showed reduced cisplatin resistance in esophageal squamous cell carcinoma [ 42 ]. Meanwhile, pretreatment whole-body total lesion glycolysis was uncovered as an independent predictor of outcomes in patients with esophageal cancer treated with definitive chemoradiotherapy [ 43 ].…”
Section: Discussionmentioning
confidence: 99%